2019
DOI: 10.3389/fmicb.2019.01874
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Ethyl 2-Nitro-3-Arylacrylates Molecules as T3SS Inhibitor Reducing the Virulence of Plant Pathogenic Bacteria Xanthomonas

Abstract: Xanthomonas oryzae pv. oryzae ( Xoo ) is a gram-negative pathogen which causes leaf blight disease. Known traditional bactericides are not much more effective in inhibiting this bacteria than before. Selecting the virulence factor of the bacteria as the target without affecting their growth has been considered as a novel method for developing new anti-microbial drugs. Type III secretion systems (T3SS) are one of the important and highly conserved virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…Ethyl 2-nitro-3-arylacrylates ( Figure 8 ) were another group of Xoo T3SS inhibitors screened by Jiang et al [ 122 ]. Molecules I-9, I-12, and I-13 showed good frontal inhibition of Xoo T3SS and exhibited strong inhibition against the hpa1 promoter, with a reduction of over 80% at 100 μM.…”
Section: Synthesized Inhibitors Of T3sssmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethyl 2-nitro-3-arylacrylates ( Figure 8 ) were another group of Xoo T3SS inhibitors screened by Jiang et al [ 122 ]. Molecules I-9, I-12, and I-13 showed good frontal inhibition of Xoo T3SS and exhibited strong inhibition against the hpa1 promoter, with a reduction of over 80% at 100 μM.…”
Section: Synthesized Inhibitors Of T3sssmentioning
confidence: 99%
“…Molecules I-9, I-12, and I-13 showed good frontal inhibition of Xoo T3SS and exhibited strong inhibition against the hpa1 promoter, with a reduction of over 80% at 100 μM. Three inhibitors at a concentration of 100 µM were co-cultured with Xoo PXO99 and did not inhibit bacterial growth [ 122 ]. At the same concentration, the three inhibitors effectively blocked Xoo T3SS hypersensitivity to tobacco.…”
Section: Synthesized Inhibitors Of T3sssmentioning
confidence: 99%
See 1 more Smart Citation
“…The virulence factors of phytopathogenic bacteria, especially Xanthomonas spp., are extremely important in the infection process . For instance, Xoo cells can protect themselves from disadvantageous environmental conditions and beneficially attack host plants by producing a series of virulence factors, including extracellular polysaccharide (EPS), adhesins, extracellular enzymes, and effectors of the type III secretion system (T3SS). , In particular, EPS, as a major virulence factor, can facilitate colonization of the plant by Xoo and prevent Xoo from being recognized by host plants . Biofilm formation, which can increase the pathogenicity of plant pathogens in the bacterial infection process, has been recently shown to be an essential factor for producing bactericide resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the plant phenolic compounds and derivatives p-coumaric acid (PCA), cinnamyl alcohol (CA),and trans-4-hydroxycinnamohydroxamic acid play a role in the inhibition of T3SS expression of D. dadantii 3937 ( Li et al, 2009 , 2015 ; Joshi et al, 2021 ). Plant phenolic compounds and derivatives such as o-coumaric acid, trans -2-phenylcyclopropane-1-carboxylic-acid, trans -2-methylcinnamic acid, and trans -2-methoxycinnamic acid as well as synthetic compound ethyl 2-nitro-3-arylacrylates, have been reported to affect the expression of X. oryzae T3SS genes ( Fan et al, 2017 ; Jiang et al, 2019 ). Khokhani et al (2013) found T3SS inhibitors (4-methoxy-cinnamic acid and benzoic acid) and T3SS inducers [ trans -2-(4-hydroxyphenyl)-ethenylsulfonate] change the expression of E. amylovora T3SS through HrpS-HrpL pathway, and salicylic acid (SA) inhibits hrpA promoter activity.…”
Section: Introductionmentioning
confidence: 99%